Pudarnya Pesona Bahasa Indonesia Di Media Sosial (Sebuah Kajian Sosiolinguistik Penggunaan Bahasa Indonesia) - Nazwa Fitriana; Achmad Zulfikar Siregar (Jurnal Sosial Politik dan Hukum, 2025)
The charm of bahasa Indonesia (Indonesian language) is decreasing due to the increasing amounts of social media platforms. Warganet Indonesian term of social media users- uses slang or new vocabulary that is not accordance with the Indonesian language system. As the consequences, the spoken and written language of Indonesian society are being affected. The warganet's language use in their social media platforms' status seen from the sociolinguistics perspective becomes the focus of the study. Warganet have 15 types of Bahasa Indonesia use in their social media platforms. There are three factors that influence the use of bahasa Indonesia i.e. 1) society, 2) self-esteem, and 3) advertisement. The way warganet use Bahasa Indonesia in their social media platform will threaten the purity of bahasa Indonesia. Young generation will prefer to use slang to the bahasa Indonesia based on the language system. Moreover, there is also possibility that they might not even know the right Indonesian language system. Therefore, there are 10 ways to preserve the charm of bahasa Indonesia from extinction. This study is conducted in order to give knowledge to the readers about the development of bahasa Indonesia in the millennial era as the increasing of social media platforms.